Research on factors that contribute to employee’s awareness on office ergonomics at Permodalan Nasional Berhad / Norhidayah Roseli - Roseli, Norhidayah (Faculty of Business and Management, 2010)
Office ergonomics is important because with the correct workstation setup we can be more productive, efficient, and best of all minimize the risk of acquiring a Musculoskeletal Disorder (MSD) that can be painful and burdensome. The purpose of this research is to examine the factors that contribute to employees’ awareness on office ergonomics at Permodalan Nasional Berhad. The strongest factors that contribute to employee’s awareness were identified which are training, knowledge and employer commitment. Descriptive study has been conducted to find out the real factors or causes to the problems and past researcher literature were being bench marking in order to conduct this study successfully. 125 questionnaires have been distributed among employees. As a result, shows that the most factors that influence the dependent variable which are training and knowledge. This research also illustrates several recommendations for management and employer on how to increase employees’ awareness on office ergonomic and also to help the company to reduce their medical bills in a long term and provide safety and health environment towards their employees.